Silicon nanoforms in crop improvement and stress management. (October 2022) - Dhakate, Priyanka; Kandhol, Nidhi; Raturi, Gaurav; Ray, Priyanka; Bhardwaj, Anupriya; Srivastava, Aakriti; Kaushal, Laveena; Singh, Akanksha; Pandey, Sangeeta; Chauhan, Devendra Kumar; Dubey, Nawal Kishore; Sharma, Shivesh; et al.
Abstract: Although, silicon – the second most abundant element in the earth crust could not supersede carbon (C) in the competition of being the building block of life during evolution, yet its presence has been reported in some life forms. In case of the plants, silicon has been reported widely to promote the plant growth under normal as well as stressful situations. Nanoform of silicon is now being explored for its potential to improve plant productivity and its tolerance against various stresses. Silicon nanoparticles (SiNPs) in the form of nanofertilizers, nanoherbicides, nanopesticides, nanosensors and targeted delivery systems, find great utilization in the field of agriculture. However, the mechanisms underlying their uptake by plants need to be deciphered in detail. Silicon nanoformss are reported to enhance plant growth, majorly by improving photosynthesis rate, elevating nutrient uptake and mitigating reactive oxygen species (ROS)-induced oxidative stress. Various studies have reported their ability to provide tolerance against a range of stresses by upregulating plant defense responses. Moreover, they are proclaimed not to have any detrimental impacts on environment yet. This review includes the up-to-date information in context of the eminent role of silicon nanoforms in crop improvement and stress management, supplemented with suggestions for future research in this field. Graphical abstract: Image 1 Highlights: Silicon nanoforms improve growth and plant productivity. Silicon nanoforms have capability to improve tolerance against various stresses and disease. Nanoforms of silicon are more effective than silicon. They positively regulate antioxidant pools and content of reactive Oxygen Species (ROS) in plants.